Relational and Spiritual Dimensions of Parental Grieving - Klaassen, Derrick W.; Young, Richard A.; James, Susan (Canadian Journal of Counselling and Psychotherapy, 2014)
This investigation explored parental grieving as a relational and spiritual process. Five couples participated in three sets of interviews over the course of approximately three months. Data were collected and analyzed using the qualitative action-project method. The findings revealed that couples grieved extensively in the context of their relationships. Grieving was facilitated through planned and spontaneous activities, and was impeded by disconnection from the loved ones and life stressors. Grieving was intimately connected to the parents’ spiritual lives, which shaped continuing bonds, offered comfort and meaning, and provided an avenue to express distress. The findings yield implications for clinical work and further research with bereaved parents.